IMPLEMENTASI ARSITEKTUR ISLAM PADA MASJID DI KOTA KENDARI - La Pande Jurumai; Wa Ode Ulfa Uzia; Sri Muliani (Jurnal PROYEKSI: Arsitektur dan Perencanaan, 2022)
Islamic architecture is a building work of art that follows Islamic principles, sourced from the Qur'an, as-Sunnah, the Prophet's Family, Companions, Ulama and Muslim scholars. This thought is poured on the physical and metaphysical of the building. Islamic architecture has existed since the time of the Prophet Ibrahim.a.s. and spread all over the world. One type of building which is the main product of Islamic architecture is the mosque. To identify Islamic architecture, it can be seen from several elements such as domes, calligraphy and mihrab. For the research method that we used in this study in the form of field observations and visual observations which were then followed by building weights from several elements such as door and window openings. As for the collection of mosque data, we obtained it from several locations in the city of Kendari. The purpose of this study is to determine the alignment of mosques in Kendari with Islamic principles, both physically and metaphysically. In addition, this study also aims to determine the influence and adaptation of Islamic architecture with other architectural concepts in mosques in Kendari. From the results of the study it can be concluded that the mosque in the city of Kendari has its own uniqueness with the implementation of Islamic architecture which is combined with both traditional and modern architectural concepts. The point that can be captured is that Islamic architecture is an adaptive and efficient architecture.